Water distribution modeling - Walski, Thomas M; Chase, Donald V. (Donald Vincent), 1960-; Savic, Dragan, 1960- (Waterbury, CT, U.S.A. : Haestad Press, 2001)
CD-ROM contains: WaterCAD software -- Exercise-examination booklet
9.1 The Role of Models in Operations -- 9.2 Low Pressure Problems -- Identifying the Problem -- Modeling Low Pressures -- Finding Closed Valves -- Solving Low Pressure Problems -- 9.3 Low Fire Flow Problems -- Identifying the Problem -- Solutions to Low Fire Flow -- 9.4 Adjusting Pressure Zone Boundaries -- 9.5 Taking a Tank Off-Line -- Fire Flows -- Low Demand Problems -- 9.6 Shutting Down a Section of the System -- Representing a Shutdown -- Simulating the Shutdown -- 9.7 Power Outages -- Modeling Power Outages -- Duration of an Outage -- 9.8 Power Consumption -- Determining Pump Operating Points -- Calculating Energy Costs -- Multiple Distinct Operating Points -- Continuously Varying Pump Flow -- Developing a Curve Relating Flow to Efficiency -- Variable-Speed Pumps -- Using Pump Energy Data -- Understanding Rate Structures -- 9.9 Water Distribution System Flushing -- Modeling Flushing -- Representing a Flowed Hydrant -- Hydrant Location Relative to Nodes -- Steady-State vs. EPS Runs -- Indicators of Successful Flushing -- 9.10 Sizing Distribution System Meters -- Subsystem Metering -- Using Models for Meter Sizing -- Implications for Meter Selection -- 9.11 Models for Investigation of System Contamination -- 9.12 Leakage Control -- Discussion Topics and Problems -- Appendix A Units and Symbols -- Appendix B Conversion Factors -- Appendix C Tables
Includes bibliographical references (pages 413-428) and index
Keywords: Water -- Distribution -- Mathematical models; Water Supply; Models, Statistical